Effect of increasing CO₂ on the terrestrial carbon cycle - Schimel, David; Stephens, Britton B.; Fisher, Joshua B. (Proceedings of the National Academy of Sciences - PNAS, 2015)
Significance Feedbacks from terrestrial ecosystems to atmospheric CO ₂ concentrations contribute the second-largest uncertainty to projections of future climate. These feedbacks, acting over huge regions and long periods of time, are extraordinarily difficult to observe and quantify directly. We evaluated in situ, atmospheric, and simulation estimates of the effect of CO ₂ on carbon storage, subject to mass balance constraints. Multiple lines of evidence suggest significant tropical uptake for CO ₂, approximately balancing net deforestation and confirming a substantial negative global feedback to atmospheric CO ₂ and climate. This reconciles two approaches that have previously produced contradictory results. We provide a consistent explanation of the impacts of CO ₂ on terrestrial carbon across the 12 orders of magnitude between plant stomata and the global carbon cycle. Feedbacks from the terrestrial carbon cycle significantly affect future climate change. The CO ₂ concentration dependence of global terrestrial carbon storage is one of the largest and most uncertain feedbacks. Theory predicts the CO ₂ effect should have a tropical maximum, but a large terrestrial sink has been contradicted by analyses of atmospheric CO ₂ that do not show large tropical uptake. Our results, however, show significant tropical uptake and, combining tropical and extratropical fluxes, suggest that up to 60% of the present-day terrestrial sink is caused by increasing atmospheric CO ₂. This conclusion is consistent with a validated subset of atmospheric analyses, but uncertainty remains. Improved model diagnostics and new space-based observations can reduce the uncertainty of tropical and temperate zone carbon flux estimates. This analysis supports a significant feedback to future atmospheric CO ₂ concentrations from carbon uptake in terrestrial ecosystems caused by rising atmospheric CO ₂ concentrations. This feedback will have substantial tropical contributions, but the magnitude of future carbon uptake by tropical forests also depends on how they respond to climate change and requires their protection from deforestation.